Geographical Inequity Among Youth Aging out of Foster Care: A Quantitative Examination of Cohort 3 of the NYTD - Goforth, Nadia (My University, 2024)
Each year, it is estimated that more than 250,000 children enter the United States foster care system (NFYI, 2024). The Annie E. Casey Foundation notes that children enter the system because their families are in crisis. Often, children have experienced unsafe conditions, abuse, neglect, or have parents who are unable to care for them. The foster care system is intended to provide a safe, temporary living arrangement and support services for children who have been removed from their families (Annie E. Casey Foundation, 2024).